Frame "Social Activities to Achieve the Goal": Formation and Specifics of Its Representation at Language Level - Kuzmicheva, Vita A.; Prokhorova, Olga N.; Dekhnich, Olga V.; Pugach, Vladimir S.; Chebotareva, Irina M. (International Journal of Criminology and Sociology, 2022)
The proposed article is devoted to describing the specifics of the frame formation "social activity to achieve the goal" represented by the verbal tokens (achieve, accomplish, attain, gain, succeed in, obtain, manage, strive, etc.) with the corresponding meaning and revealing the dependence of the modification of their meaning on the intrasystem and extra system restructuring of the proper frame.